Dinding kata sebagai media pengembangan perbendaharaan kosakata siswa MI Al Abrar Makassar - Nensilianti Nensilianti; Suarni Suarni (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purposeof this activity is to open up theteacher's insight that vocabulary mastery in students is veryimportant to sustain their success in learning and to trainteachers to design/ create word wall media with variations anduse it interestingly in teaching students. These puroses arebased on the problems faced by teachers of MI Al AbrarMakassar that students' understanding of the vocabulary ateach grade level is still far from ideal or still under theminimum that students must have which causes them quitedifficult to achieve a basic curriculum competency and thereare still inadequate levels of teaching skills, especiallyclassroom management skills, skills in choosing and usingstrategies and also skills in making or developing vocabularylearning media of teachers in MI Al Abrar Makassar. Thistraining is expected to inspire teachers about various types ofword media (word wall) and how to use them to developstudents' vocabulary mastery which has an impact on students'reading and writing skills. With word wall media, students willbe triggered to be more active, enthusiastic in learninglanguage, especially learning vocabulary which is considereddifficult. Therefore, this learning media will help learningactivities and students can achieve maximum results. Thistraining was held at MI Al Abrar Makassar invloved 18teachers of first grade 1 to sixth grade. As the follow-up of thisactivities, the further targets for the next training will be thefirst graders and sixth graders in academic year 2017-2018school year. To solve the teachers' problems, it is pursued inthree stages of activities, namely workshop/ training,mentoring, and reflection/ refinement which are packaged inthe form of Teacher Working Group (KKG) of Madrasahlesson study.